Characterization of language disorders in children with lead poisoning - Gahyva, Dáphine Luciana Costa; Crenitte, Patrícia de Abreu Pinheiro; Caldana, Magali de Lourdes [UNESP]; Hage, Simone Rocha de Vasconcellos (FapUNIFESP (SciELO), 2008)
Background: lead poisoning can have a negative impact on the neuropsychological functions, including language, due to the damage it causes to the developthent of the Central Nervous System. Aim: to verify the occurrence of language disorders in children who suffered from led poisoning and to verify the correlation between the lead concentration level in the blood and the language disorders presented by the children. Method: language evaluation of 20 preschoolers, with lead concentration level in the blood above 10μg/dl. Results: 13 children presented language impairment involving only phonology or more than one language subsystem. The statistical analysis indicated that no correlation exists between the severity of the language impairment and the concentration levels of lead. Conclusion: the number of children with language impairment indicates lead poisoning as a risk factor for the present alterations, even though other risk factors for language disorders were found and the absence of correlation between the investigated variables.
Keywords: Cognition; Language development disorders; Lead poisoning